Re- Examining Three Theories Presented by Jurisprudents on the Nature of Matrimony Contract and the Effects of Views on Marriage Issue - Mansour Amirzadeh jirkoli (فقه و حقوق خانواده)
One of the main issues on matrimony contract is the nature of this contract. Three well-known theories have presented among Shi’a jurisprudents, and even Jurists in this regard. While some jurisprudents consider it as mutual interest contract, some others consider it as non-mutual interest contract. However, the great men, such as Na’eini, knew it semi-mutual interest nature. Also, some jurists describe it as partnership contract. The writer argues that it is a “special contract”.  It seems that the differences between these theories are rooted in various aspects of marriage, i.e. contractual aspect and devotional and ethical aspect. The purpose of this research is to critically examine the above-mentioned theories. In this regard, first the theoretical bases of these theories are examined, then the effect of these views on certain marriage issues such as “contract by conduct”, “The wife’s right of lien”, and “option of cancellation of marriage” has been studied by descriptive- analytical method and by collecting data from library. The most important findings are the following: matrimony is not a mutual interest contract; it is a “special contract”. Those who believe in the former do not exercise the decrees related to most marriage related issues including contract by deed, and means of marriage cancellation. The legislation of the wife’s right of lien, affected by the famous theory by Shi’a jurisprudents on the nature of matrimony contract, considers it a mutual interest contract.